"God Spoke to Me": Subjective Paranormal Experience and the Homeostatic Response to Early Trauma. (March 2021) - Marks, David F.
The prevalence of reported subjective paranormal experience (SPE) is at high levels in all populations investigated to date. This article presents a new integrative theory of SPE in light of the brain's homeostatic response to early trauma. I hold that developmental factors in the brain's responses to trauma predispose victimized individuals towards SPE and paranormal beliefs. I examine the reported associations between childhood abuse, dissociation, depersonalization, compartmentalization, fantasy generation, homeostasis and SPE. A new integrative theory of psychological homeostasis draws upon the mechanisms of dissociation and fantasy generation to explain the origins of SPE. Twelve hypotheses from the Homeostasis Theory are found to be consistent with the findings of multiple studies and falsifying evidence has yet to be identified. Freezing and associated releases of fantasy, which may take the form of SPE, serve as a survival strategy in the homeostatic regaining of safety and control following childhood abuse. Prospective research is necessary to deepen our understanding of the brain mechanisms required by the system described here.